Work-life balance of women in urban area of China: Experiences of women who return to their paid work after having babies. - ZHAO, DANNAN (2016)
The study explores the experience of women in urban China who go back to their paid jobs following the birth of their child. Semi-structured with 10 interviewees was used to record and collect data in conversations. A good amount of information generated from interviews indicated that in urban China, working mothers considered the transition period as challenging and perceived many difficulties in balancing their work and family. They took on dual roles – employees and mothers. In addition, supports from family, workplaces and the Chinese government were also discussed and women provided their expectations on supports. Chinese traditional ideology about the role of women and their responsibilities showed impacts on the experience of working mothers considerably. The influence from the old generation also played an important role in women’s decisions.